Correlation of uterine scoring system for reproduction with pregnancy rate among infertility patients undergoing intracytoplasmic sperm injection and frozen-thawed embryo transfer - U., Yashila Prithika; Saravanan, Mahalakshmi; Sharma, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Successful implantation requires presence of a good quality embryo and receptive endometrium. Endometrial receptivity is ability of endometrium to successfully attach embryo, nourish and keep it alive. Sonographic findings are weighed according to uterine scoring system for reproduction (USSR) or uterine biophysical profile (UBP) by Applebaum. It has become absolute necessity to evaluate uterus and endometrium prior to embryo transfer, so that optimum results are obtained in favourable uteri. Methods: It is a prospective observational study which includes 100 patients undergoing intracytoplasmic sperm injection (ICSI) treatment followed by frozen embryo transfer. The Applebaum scoring system was done on the day of thawing scan, using ultrasonography (USG) and Doppler studies, assessing endometrial thickness, endometrial motion, endometrial layering, myometrial contractions, uterine artery doppler flow, endometrial blood flow in zone 3 and myometrial blood flow – the scores of each parameter was noted, the final score calculated. Results: Receiver operating characteristic curve (ROC) curve total score in Applebaum scoring system for predicting pregnancy has a cut-off- 13 with sensitivity- 90.10%, specificity- 89.5%, positive predictive value (PPV)-97.34%, and negative predictive value (NPV)- 67.95. The above should be incorporated into routine practice. This was suggested by our study results in addition to endometrial patterns. Conclusions: Applebaum’s USSR scoring system is a simple and non-invasive method for prediction of pregnancy rate in ICSI and frozen embryo transfer cycle. Uterine scoring system will help to perform embryo transfers in only favourable uteri and postpone or cancel those cycles in which poor uterine score is demonstrated.